GIS based evaluation of social determinants of children's health in Turkey: Case study of Istanbul - Dogru, A. Ozgur; Kahraman, Ash; Seker, Dursun Zafer; Sivri, Nuket (Elsevier BV, 2019)
Basic elements considered as social determinants of the health varies in political, socio-economic, structural and intermediary contexts. While socio-economic and political contexts are directly related with the social, economic, public and health policies in country scale. The structural context additionally includes socio-economic dimensions such as income, education, occupation, social class, gender and race/ethnicity. In addition to these basic determinants, the public health, and especially the children health is also affected by the intermediary determinants, which are material circumstances including physical conditions of the working, housing and neighborhood environments and consumption potential (i.e. healthy foods, proper clothing etc.). Existing experiences provided that, the children who grow up on low socioeconomic conditions or on inappropriate environmental conditions including the residential structures tend to become more often ill than the children living in better environmental and socio-economic conditions. This situation reveals the importance of the city planning in terms of providing better conditions for children's health. This study aims to evaluate the social determinants of children's health by the use of Geographic Information System (GIS) technology. For this purpose, a variety of social determinants in terms of political (quality and quantity of health services), structural (education and social class) and intermediary (physical environment, housing, and neighborhood) contexts were examined in Bakırköy and Esenler districts, which are located European side of Istanbul. For this purpose, 2017 dated official dataset including census information and the statistics on the quality and the quantity of the education and health services in two districts were used for examining the political and structural determinants. The spatial characteristics of the physical environment and housing conditions in the study area were constructed from cadastral maps and development plans by use of GIS tools. As a last step, children's health data that consists of pediatric patient visits and diagnosis reports from 12 hospitals in Bakırköy and Esenler districts were also examined for understanding the potential relationships between the social determinants and existing health conditions. Results of this research revealed that the Bakırköy district has better conditions in terms of all health determinants when compared with Esenler district. Therefore, the health status of children living in Bakirköy is expected to be better than those living in the Esenler, which coincides with the evaluation of official children health data.
Keywords: Turkey; Social Determinants of Health; Air-Pollution; Child Health; Environmental Exposure; GIS; Children's health; Socioeconomic Factors; Residence Characteristics; Geographic Information Systems; Humans; Social determinants; Child